Factors Influencing Blended Personalized Arabic Language Learning - Ahmad Said Bataineh, Rania; Din, Rosseni; Othman, Nabilah; Al Mashakbh, Atef (International Journal of Engineering and Technology, 2018)
Foreign students learning Arabic language face problems regarding writing, reading, speaking and listening. This study uses learning modules over the Facebook social media which allow interactivity among learners and facilitators to help them improve the four skills. In addition, learning Arabic is also crucial to others in order to meaningfully understand Al-Quran, the Holy Book for Muslims from all over the world. The quest for effective learning strategies and instructional approach in learning Arabic as a foreign language has been a challenge for educators. Studies have shown that student centered learning must be the approach in any effective language learning to cater for each individual to achieve the learning outcome. The main focus of this study is to identify factors influencing a personalized blended approach for learning Arabic language. A survey was administered on 157 foreign Arabic learners and SEM-PLS 3.0 software was use to identify reliability, validity and factors influencing blended personalized arabic language learning and the contribution of blended learning towards personalized learning. The results showed (i) evidence of a five-dimension measurement model contributing to blended learning, (ii) evidence of a four-dimension measurement model contributing to personalized learning, and (iii) a relationship showing positive impact of blended learning with significant effect on personalized learning at the (.01) level of significance (β = 0.757, t = 16.283, p < .01), and (iv) evidences of a reliable and valid model for a blended personalized learning model for Arabic Language Learning. The result also showed that personalization of Arabic as a foreign language learning supported language learning through empowering learners to build up their knowledge and enables them to think critically, work in teams and solve problems collectively. In a blended learning environments learners had the opportunity to actively interpret their experience using internal cognitive operations via the practice of reflective exercises embedded into their Facebook groups’ timeline. In this study, a blended combination of face-to-face, self-learning and computer-mediated communication was used. Blended learning indeed contributes to personalization of learning the Arabic language. Moreover, learners were in charge and in control of their learning. Learners collaborated and socially interacted with others. This enabled them to construct knowledge and gained significant learning.